Characterization and Serotyping of Three Feline Reovirus Isolates - Csiza, C. K. (1974)
Three feline virus isolates were shown to be members of the reovirus group by their growth characteristics in cell cultures, physicochemical properties, and appearance under an electron microscope. Their close serological relationship to, or identity with, human reovirus type III was revealed by hemagglutination, hemagglutination inhibition, serum neutralization, and gel diffusion tests. One feline isolate (636) was pathogenic for suckling mice.